THE EFFECTIVENESS OF INTEGRATED HAJJ INFORMATION AND COMPUTERIZATION SYSTEM (SISKOHAT) IN THE HAJJ PILGRIMAGE IN SUMEDANG REGENCY - Febianti, Fepi; Farida, Ida (UNIVERSITAS PAKUAN, 2020)
This study aims to analyze the effectiveness of the integrated Hajj information and computerization system (SISKOHAT) in the hajj pilgrimage in Sumedang Regency. This research uses a descriptive method, which is a method of one type of research whose purpose is to present a complete picture of the social setting or what is meant by exploration and clarification of a phenomenon or social reality, by describing the variables relating to the problem and the unit understudy with the phenomenon that is tested. The informants are the Head of the Office, the Head of Haj and Umrah Services, the Hajj and Umrah Service Unit Employees, and the SISKOHAT Operators. Based on the results of the research, the effectiveness of the integrated hajj information and computerization system in organizing the hajj pilgrimage has been going well, but there are still obstacles, namely the service support factor or a network from SISKOHAT, as well as people's understanding of the system. Strategies or efforts to ensure the effectiveness of SISKOHAT in carrying out the hajj properly are as follows: holding cooperation or MOU with local governments to improve network quality, organizing education and training, technical guidance or other training to improve employee integrity, and collaborating with extension workers at KUA and KBIH to provide understanding to the community or prospective pilgrims. Suggestions put forward for the effectiveness of the SISKOHAT in organizing the hajj run well are as follows: improving the quality of the SISKOHAT network to minimize existing obstacles. Also, it is necessary to hold comprehensive socialization for the community regarding the implementation of the hajj pilgrimage in Sumedang Regency, especially regarding hajj pilgrimage services using SISKOHAT.